TERAPI AKTIVITAS KELOMPOK (TAK) MEWARNAI UNTUK MENURUNKAN TINGKAT STRES PADA LANSIA DI WISMA JERUK PANTI SOSIAL TRESNA WERDHA BUDI MULIA 2 CENGKARENG – JAKARTA BARAT - Siti Robeatul Adawiyah; Nandini Audrianingsih; Muhammad Iqbal; Ahmad Fauzan H; Reza Shintia L; Dwiyanti Putri P. N; Siti Nurotul Faizah. F; Ilma Syafna F; Habibatus S; Maretha Fajri A (Yayasan Nusantara Hasana Berdikari, 2023)
Background: Elderly or elderly is someone who has entered the age of 60 years or the final stage of his life. A person can be said to be elderly because there has been a process called the aging process or aging process (World Health Organization, 2019). The elderly experience gradual physical and psychological deterioration, where the decline in the condition can cause stress in some of the elderly. Psychosocial problems in the elderly can include stress, anxiety (anxiety) and depression. The problem comes from several aspects, including changes in physical, psychological and social aspects. Goal: after coloring activities can make the elderly visit to the doctor less and reduce health problems. Not only that, there are several other benefits that can be obtained through these coloring activities. Among them, it makes sleep more quality and reduces pain and anxiety. (Alhawari &; Ayu Pratiwi, 2021). Method: Group activity therapy using coloring media. Time and place: the activity will be carried out on Thursday, June 8, 2023, at 09.00 until finished at Wisma Jeruk Lemon, Budi Mulia 2 Nursing Home Cengkareng – West Jakarta. . Results: after coloring therapy, the most elderly stress levels were normal 6 elderly, and mild stress 4 elderly. There are no more elderly who experience severe and very severe stress, there is an effect of providing group activity therapy (coloring) on the psychological stress of the elderly at Wisma Jeruk, Tresna Werdha Budi Mulia Social Institution 2.